PENGUKURAN KINERJA KARYAWAN DARI KOMITMEN NORMATIF DAN MOTIVASI KERJA (STUDI PADA BAGIAN KANTOR PT. KERTA RAJASA RAYA) - RIFKY FIRDIAS, AHMAD (Jurnal Ilmu Manajemen (JIM), 2020)
This study aims to determine and explain the effect of normative commitment and work motivation on employee performance (study in the office of PT. Kerta Rajasa Raya). This research is a type of causality research using a quantitative approach. The saturated samples used for sampling techniques with 46 respondents in the office of PT. Kerta Rajasa Raya. The Structural Equation Model (SEM) with the help of smart PLS 3.0 software used in this study for statistical analysis. The results of this study indicate that normative commitment does not significantly influence employee performance, work motivation has a positive and significant effect on employee performance. Keywords: employee performance; normative commitment; work motivation.